Genetic Screening Test to Detect Translocations in Acute Leukemias by Use of Targeted Locus Amplification. (1st July 2018) - Alimohamed, Mohamed Z; Johansson, Lennart F; de Boer, Eddy N; Splinter, Erik; Klous, Petra; Yilmaz, Mehmet; Bosga, Anneke; van Min, Max; Mulder, André B; Vellenga, Edo; Sinke, Richard J; Sijmons, Rolf H; et al.
Abstract: BACKGROUND: Over 500 translocations have been identified in acute leukemia. To detect them, most diagnostic laboratories use karyotyping, fluorescent in situ hybridization, and reverse transcription PCR. Targeted locus amplification (TLA), a technique using next-generation sequencing, now allows detection of the translocation partner of a specific gene, regardless of its chromosomal origin. We present a TLA multiplex assay as a potential first-tier screening test for detecting translocations in leukemia diagnostics. METHODS: The panel includes 17 genes involved in many translocations present in acute leukemias. Procedures were optimized by using a training set of cell line dilutions and 17 leukemia patient bone marrow samples and validated by using a test set of cell line dilutions and a further 19 patient bone marrow samples. Per gene, we determined if its region was involved in a translocation and, if so, the translocation partner. To balance sensitivity and specificity, we introduced a gray zone showing indeterminate translocation calls needing confirmation. We benchmarked our method against results from the 3 standard diagnostic tests. RESULTS: In patient samples passing QC, we achieved a concordance with benchmarking tests of 81% in the training set and 100% in the test set, after confirmation of 4 and nullification of 3 gray zone calls (in total). In cell line dilutions, we detected translocations in 10% aberrant cells at several genetic loci. CONCLUSIONS: Multiplex TLA shows promising results as an acute leukemia screening test. It can detect cryptic and other translocations in selected genes. Further optimization may make this assay suitable for diagnostic use.